Особливості моделювання автономної сонячної фотоелектричної системи - Фетюхіна, Людмила Вікторівна; Бутова, Ольга Анатоліївна; Булавін, Максим Сергійович (Національний технічний університет "Харківський політехнічний інститут", 2016)
В роботі представлено імітаційне моделювання автономної сонячної фотоелектричної (PV) системи в програмному середовищі Matlab/Simulink. Розглянуті особливості побудови таких систем. Об'єктом дослідження є PV-система, в якій застосовано TWC алгоритм для знаходження точки максимальної потужності при різних умовах навколишнього середовища, а також його використання для керування перетворювачем. Перевірка розробленого програмного забезпечення для мікроконтролеру STM32F407VG на демонстраційній платі підтвердила працездатність алгоритму.

Purpose. This paper describes a simulation model of standalone solar PV energy conversion system Thе paper presents mathematical models to study and prognosis of the behavior of solar PV-system by changing climatic and physical parameters of the solar panels. Methodology. A maximum power point tracking (MPPT) algorithm based on method Three Point Weight Comparison is applied to extract the maximum power from solar PV energy conversion system. This method uses the increasing conductivity of array of PV modules for computing power sign changes in relation to voltage. A simulation model based on mathematical model is constructed using Matlab/Simulink. Results. Results from simulation are stated to demonstrate the behaviour of standalone solar PV energy conversion system depending on the intensity of solar radiation, temperature, power of solar battery. The simulation results showed that due to the inertia of the reactive elements algorithm (block MPPT) is forced to constantly adjust the PWM signal. The output parameters of inverter when dynamic changes of parameters were not significantly changed by changing the input parameters of solar panels, guaranteeing a stable supply of consumers. Originality. MPPT block has been synthesized, which implements the converter control algorithm that enabled the further system the modeling. Software of microcontroller STM32F407VG is developed, which selects the maximum power from the solar cell and the generation of sine wave voltage. Practical value. The developed software of microcontroller STM32F407VG been tested demonstration board that allows its use for further research. The algorithm MPPT method is verified through simulation and experiment in various conditions.
Features of simulation of the standalone solar photovoltaic system
Keywords: сонячна батарея; точка максимальної потужності; вольт-амперні характеристики; інвертор напруги; система керування; мікроконтролер; solar cell; maximum power point; current-voltage characteristics; voltage inverter; Matlab; system control; microcontroller